Effect of solvents on the morphology and performance of Polyethersulfone (PES) polymeric membranes material for CO2/CH4 separation - Ahmad, M.S. (Institute of Physics Publishing, 2018)
Membrane technology has several advantages such as the ability to separate chemical species within compact plant footprints, low thermal energy requirements and simple process flow schemes. By optimizing the available materials and analysis, this work comes with the objective to synthesize the polymeric membrane, which has the best separation performance. In this work, three (03) membranes have been synthesized and a comparative analysis were conducted based on different types of solvent namely N, N-dimethylacetamide (DMAc), N, N-dimethylformamide (DMF), N-methyl-2-pyrrolidinone (NMP). In characterizing the synthesized membrane, Thermo Gravimetric Analysis (TGA), Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transform Infrared Spectroscopy (FTIR) analysis were used. A comparative study was carried out to compare the effects of each solvent towards CO2 separation performance. Â© Published under licence by IOP Publishing Ltd.